(untitled) (Bangladesh Agronomy Journal, 2022)
The experiment was conducted in Boro season, 2020-21 to compare the performance of fortified rice variety BRRI dhan84 with non-fortified mega variety BRRI dhan89 and their suitable combinations for maximum growth and yield. Treatments were: two rice variety viz., i) BRRI dhan84 (V1) and ii) BRRI dhan89 (V2) in the main plot and seven different fertilizer management viz., i) No fertilizer (F1), ii) Recommended NPKS (RFD) with Zn as basal (F2), iii) RFD + Zn as foliar at anthesis (F3), iv) RFD + Zn & B as foliar at anthesis (F4), v) 50% RFD + 50% Cowdung as basal (F5), vi) 50% RFD + 50% Cowdung + Zn & B as basal (F6) and vii) 50% RFD + 50% Cowdung as basal + Zn & B as foliar at anthesis (F7) in the sub-plot. The experiment was laid out in a Split-plot design having 3 replications. No significant variations observed between the two varieties for almost all the studied characters except filled grains panicle-1 where the variety BRRI dhan89 showed higher number of grains (116.14) than the other variety. Foliar application of zinc and born (F4) gave the highest plant height (102.54 cm), effective tillers hill-1 (12.83) that similar (13.00) with F2 (recommended NPKS with Zn as basal), panicle length (25.91 cm), 1000-grain weight (23.58 g), grain yield (7.67 t ha-1), biological yield (14.85 t ha-1) and harvest index (51.69%). The interaction of V2F4 and V1F4 resulted superior response for almost all the studied parameters. Foliar application of zinc and boron (F4) along with RFD increased 8.79 and 27.45% yield in BRRI dhan89 compared to that of foliar (F3) and basal (F2) application of zinc, respectively that was 17.11 and 26.77% for the other rice variety BRRI dhan84. Bangladesh Agron. J. 2022, 25(1): 97-103